Mobility for learners and staff – higher education students and staff mobility inter-institutional agreement 2014-21 between programme countries – Universitat Politècnica de Catalunya and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2015)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme; - Erasmus subject area - Architecture